Typowe czy wyjątkowe? Odkrywane elementy wystroju średniowiecznej architektury Torunia - Pilecka, Elżbieta (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2016)
The aim of this article is to present the little – known elements of architectural and coloristic design which were revealed during the restoration work in Toruń within the last years. However, these are not the “great art” monuments but as so-called “pictorial media” – they should be taken into consideration widely in the framework of art history discipline. The understanding of these information signification and the analysis of preserved examples by proposed methods of the latest history of art is treated exactly as the searching postulate. From the stage of factual information gathering we ought to proceed to the reflection stage.